In vitro binding of simian immunodeficiency virus matrix protein to the cytoplasmic domain of the envelope glycoprotein - Manrique, Julieta Marina (2008)
Incorporation of the envelope (Env) glycoprotein into budding virions is a key step in the replication cycle of lentiviruses. Previously, we provided genetic and biochemical evidence indicating that Env packaging into simian immunodeficiency virus (SIV) particles is mediated by the association of the Env cytoplasmic domain (CD) with the matrix (MA) domain of Gag. In this study, we developed an in vitro binding assay that, based on recombinant proteins expressed in bacteria, allowed us to demonstrate the physical interaction between the SIV Env CD and the MA in the absence of other viral or cellular proteins.We show that this association is blocked by mutations in each of the interacting domains that have been reported to interfere in vivo with the incorporation of Env into SIV virions. Moreover, we determined that the binding of SIV MA to the Env CD is saturable with a dissociation constant of 7×10(-7) M. Interestingly, the SIV MA is capable of specifically interacting in vitro with the human immunodeficiency virus type 1 Env CD, but not with that of the distantly related feline immunodeficiency virus. Our results strongly support the notion that the association between the SIV MA and Env CD plays a central role in the process of SIV Env incorporation into Gag-made particles.